Psychological features of female ice hockey players at start of their sports careers - Rodygina, Y. K.; Potapchuk, A. A.; Matveev, S. V.; Didur, M. D. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to determine psychological and psycho-physiological features of girls during competitions at the start of their sports careers in order to obtain data about the dynamics of changes of these factors and developing guidelines regarding psychological training in women`s ice hockey.